Kisspeptin Neurons in the Infundibular Nucleus of Ovariectomized Cats and Dogs Exhibit Unique Anatomical and Neurochemical Characteristics - Rumpler, Éva; Takács, Szabolcs; Göcz, Balázs; Baska, Ferenc; Szenci, Ottó; Horváth, András; Ciofi, Philippe; Hrabovszky, Erik; Skrapits, Katalin (Frontiers in Neuroscience, 2020)
Neurons co-synthesizing kisspeptin (KP), neurokinin B (NKB) and dynorphin (“KNDy neurons”) in the hypothalamic arcuate/infundibular nucleus (INF) form a crucial component of the gonadotropin-releasing hormone (GnRH)/luteinizing hormone (LH) “pulse generator”. The goal of our study was to characterize KP neuron distribution, neuropeptide phenotype and connectivity to GnRH cells in ovariectomized dogs and cats with immunohistochemistry on formalin-fixed hypothalamic tissue sections. In both species, KP and NKB neurons occurred in the INF and the two cell populations overlapped substantially. Dynorphin was detected in large subsets of canine KP (56%) and NKB (37%) cells and feline KP (64%) and NKB (57%) cells; triple-labeled (“KNDy”) somata formed ~25% of all immunolabeled neurons. Substance P (SP) was present in 20% of KP and 29% of NKB neurons in ovariectomized cats but not dogs, although 26% of KP and 24% of NKB neurons in a gonadally-intact male dog also contained SP signal. Only in cats, cocaine- and amphetamine regulated transcript was also colocalized with KP (23%) and NKB (7%). In contrast with reports from mice, KP neurons did not express galanin in either carnivore. KP neurons innervated virtually all GnRH neurons in both species. Results of this anatomical study on ovariectomized animals reveal species-specific features of canine and feline mediobasal hypothalamic KP neurons. Anatomical and neurochemical similarities to and differences from the homologous KP cells of more extensively studied rodent, domestic and primate species will enhance our understanding of obligate and facultative players in the molecular mechanisms underlying pulsatile GnRH/LH secretion.